Lysosomal channel TPC2 modulates microglia-endothelial signaling in choroidal angiogenesis - Yi Lu; Alice Reschigna; Franz Kynast; Zhuo Yang; Maximillian Gerhardt; Pavel Kielkowski; Siegfried Priglinger; Martin Biel; Stylianos Michalakis (Angiogenesis, 2026)
Pathological choroidal neovascularization underlies vision loss in neovascular age-related macular degeneration (nAMD), yet the molecular regulators coordinating vascular and immune components remain incompletely defined. Here, we investigated the role of the endolysosomal cation channel, two-pore channel 2 (TPC2) in choroidal angiogenesis. Loss of TPC2 in mice markedly reduced ex vivo choroidal sprouting, while pharmacological activation enhanced vascular growth. Mechanistically, Tpc2 -deficiency led to downregulation of multiple microglia-derived pro-angiogenic factors and impaired the ability of the microglial secretome to stimulate neovascularization. In choroidal vascular cells, TPC2 loss attenuated NF-κB/MAPK signaling pathways. Tpc2 -deficiency is also associated with lysosomal secretion of cathepsins, especially CTSD, resulting in decreased extracellular proteolytic activity and impaired paracrine regulation of angiogenesis. Extending these findings to human cells, TPC2 knockout in iPSC-derived endothelial cells impaired migration, tube formation, and CTSD activity in the secretome, mirroring the murine phenotype. Together, these results establish TPC2 as one of the regulators of lysosome-mediated choroidal angiogenesis, highlighting its potential as a therapeutic target in nAMD.